APLIKASI AKADEMIK SISWA BERBASIS SMS GATEWAY DI SMA NEGERI 1 ENAM LINGKUNG - Rajimar Suhal Hasibuan Hasibuan; Andrew Kurniawan Vadreas (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2022)
As one of the national standard schools that goes international, SMAN 1 ENAM LINGKUNG must be able to improve the quality of its education to be better, one of which is by overcoming the problem of undisciplined students such as students who like to be truant (from home to school but not arriving at school), withdraw (go home before school hours end), and if a letter is given to call parents, students often do not convey it to their parents, even some of the students give the letter to the person they hire to represent their parents. Making this application is done on the basis of analysis and observations made at SMAN 1 Enam Lingkung with a focus on the problem of student attendance or attendance. The purpose of making this application is to be able to connect or facilitate between the school and parents in sharing information, so that parents can know the progress of their children's studies at school. This SMS Gateway-based academic application is designed using the PHP (Hypertext Preprocessor) programming language using the SDLC (System Development Life Cycle) design method with the Waterfall approach. The steps taken in this research are system analysis and planning, requirements analysis, system design, implementation, integration and testing. The results of this study are expected to help facilitate the sharing of information between schools and teachers.